Alkali‐Ion Storage Behaviour in Spinel Lithium Titanate Electrodes. Issue 11 (14th July 2015) - Pan, Huilin; Sun, Yang; Mu, Linqin; Hu, Yong‐Sheng; Chen, Liquan; Huang, Xuejie
Abstract: The alkali‐ion storage in spinel lithium titanate (Li4 Ti5 O12 ) is comprehensively investigated in this work. In Li4 Ti5 O12, Na storage is more dependent on the particle size compared to Li storage. Electrochemical results show a Na‐storage capacity from 150 to 16 mAh g −1, with increasing particle size from 50 to 500 nm, whereas the Li‐storage capacity appears to be independent of particle size. The Na‐storage rate capability in Li4 Ti5 O12 is much worse than that of Li, probably because of the sluggish Na + diffusion in Li4 Ti5 O12 . Ab initio molecular dynamics simulations also indicate that this can be attributed to the slow diffusion kinetics of Na + in spinel Li4 Ti5 O12 . Abstract : Diffusion the situation : The alkali‐ion storage in spinel lithium titanate (Li4 Ti5 O12 ) is comprehensively investigated. In Li4 Ti5 O12, Na storage is more dependent on the particle size compared to Li storage. Ab initio molecular dynamics simulations indicate that this can be attributed to the slow diffusion kinetics of Na + in spinel Li4 Ti5 O12 .